Analisis daya pengereman pada rem cakram roda depan kendaraan motor listrik e-niaga roda 3 geni biru - Saputra, Faizal Irvan (Journal of New Energies and Manufacturing, 2022)
Brakes are systems used to control, slow down and stop wheel rotation. Failures in the braking system have a very fatal impact on the driver and other drivers. Because it is very important from the function of the vehicle brake system, it is necessary to conduct in-depth research on the braking power needed so that the brake system can work perfectly and stop according to the standard braking distance. The purpose of this study is to be able to determine the amount of braking power required for the disc brake type on the blue Geni 3-wheeled E-Commerce electric motor to be able to stop the vehicle perfectly. The test method that will be used is to test the braking road with a vehicle variation speed of 20 Km / h, 30 Km / h and 40 Km / h with a maximum vehicle stop distance of 25 meters. From the results of theoretical calculations and tests on vehicleS E- obtained the results of the braking power required at a speed of 20 Km / h of 3786.97 J / s with a vehicle stop distance of 7.4 meters and a braking force of 1371 N, at a speed of 30 Km / h braking power of 7563.79 J / s with a stopping distance of 12.26 meters and a braking force of 1820 N, at a speed of 40 Km / h The braking power is 11118.25 J/s with a vehicle stop distance of 19.8 meters and a braking force of 2021.5 N